Agro-morphological and Genotypic Diversity among Rice Germplasms under Rainfed Lowland Condition - Krishna Dhakal; Ram Baran Yadaw; Bandhu Raj Baral; Keshab Raj Pokhrel; Santosh Rasaily (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
The present study was performed in a randomized complete block design with three replications to identify higher yielding genotypes and putative traits for grain yield improvement under a rainfed environment. Genotypes recorded highly significant variation for most of the observed agro- morphological traits except the number of effective tillers/m2. IR102774-31-21-2-4-7 (5.40 t/ha) followed by IR99739: 2-1-1-2-1 (5.22 t/ha), and IR103587-23-2-1-B (5.05 t/ha) respectively were the higher grain yielders. These high yielders were among the sets of early flowering (85-96 days) and maturing (120-130 days) genotypes. Plant height (PHT- 86.62% and 25.69%), harvest index (HI-87.17% and 44.66%), and thousand-grain weight (TGW- 71.06% and 30.05%) recorded high heritability values coupled with higher genetic advance as a percentage of the mean (GAM). IR102774-31-21-2-4-7 produced superior agro-morphological character for several traits like grain yield, thousand-grain weight, biological yield, plant height, and days to flowering and maturity. Plant height, biological yield, harvest index, days to flowering, and maturity were highly associated with grain yield and had medium to high heritability and GAM values. Therefore, these traits might be of importance for selection in grain yield improvement of rice under rainfed lowland conditions.